Exploring Mosquito Hazards in Bangladesh: Challenges and Sustainable Solutions (IUBAT Review, 2024)
Mosquito-borne diseases remain a persistent public health challenge in Bangladesh, posing significant burdens on individuals, healthcare systems, and socio-economic development. This review explores the multifaceted dimensions of the mosquito problem, encompassing epidemiology, vector ecology, environmental factors, and socioeconomic determinants of mosquito proliferation. To understand the disease burden, we explore the transmission dynamics and public health impact of prevalent mosquito-borne diseases like dengue, malaria, and chikungunya. Furthermore, we scrutinize the efficacy and limitations of existing vector control strategies, including their environmental implications and sustainability. The role of urbanization, climate change, and water management practices in exacerbating mosquito-breeding habitats is critically examined. This research aligns with Sustainable Development Goal (SDG) point 3 and 11. By analyzing successful mosquito control programs implemented in other countries, we aim to inform the development of evidence-based, integrated vector management strategies for Bangladesh. This approach aligns with the principles of Happy Bangladesh, emphasizing innovation, data-driven decision-making, and sustainable development. Ultimately, this review seeks to provide actionable insights for policymakers and public health practitioners to combat mosquito-borne diseases and improve the health and well-being of the Bangladeshi population.IUBAT Review—A Multidisciplinary Academic Journal, 7(2): 01-29